2016
DOI: 10.1242/jcs.190132
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal breaks during mitotic catastrophe trigger γH2AX–ATM–p53-mediated apoptosis

Abstract: There was an error published in J. Cell Sci. 124, 2951-2963.In Fig. 4C, the blot representing pATM was inadvertently duplicated as representing G3PDH. The G3PDH western blot has been replaced with the correct image in the figure shown below. There are no changes to the figure legend, which is accurate. This error does not affect the conclusions of the study.The authors apologise to the readers for any confusion that this error might have caused. Fig. 4. Increased γH2AX level during MC leads to cell death. Untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…As p21 regulates the cell cycle at the G 1 /S transition and induces G 1 phase arrest in response to a variety of stimuli, this is the likely cause of the reduced numbers of aggresome-containing cells entering mitosis. Any event in this pathway, from DSB formation, the activation of p53, and up-regulation of p21 to cell cycle arrest, can lead to caspase-dependent apoptosis (27,46,47). Driven by long term deposition of juxtanuclear aggresomes, these events may, therefore, contribute to the activation of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As p21 regulates the cell cycle at the G 1 /S transition and induces G 1 phase arrest in response to a variety of stimuli, this is the likely cause of the reduced numbers of aggresome-containing cells entering mitosis. Any event in this pathway, from DSB formation, the activation of p53, and up-regulation of p21 to cell cycle arrest, can lead to caspase-dependent apoptosis (27,46,47). Driven by long term deposition of juxtanuclear aggresomes, these events may, therefore, contribute to the activation of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to stabilization of p53, which thus promotes the transcription of cyclin-dependent kinase inhibitor p21 leading to arrest of the cell cycle at the G 1 /S transition (26) or which initiates apoptosis (27). We used immunoblotting to investigate whether P-p53 (Ser-15) is more prevalent in aggresome-containing cells and found that long term expression of EGFP-HDQ72 caused a gradual increase in P-p53 (Ser-15) levels over a 3-month period (Fig.…”
Section: Long Term Accumulation Of Aggresomes Increases the Incidencementioning
confidence: 99%
“…MNase-digestion assays, the standard method to detect DNA breaks in chromatin, showed that the pre-S 2 mutant LHBS + cells displayed increased DNA damage-induced degradation in the context of nucleosome structure, whereas the control and wild-type LHBS did not ( Figure 3E) [17]. Accumulating unrepaired DNA DSBs eventually leads to the formation of multinucleated cells, because of chromosome breakage-induced mitotic catastrophes [21]. Indeed, pre-S 2 mutant LHBS + and importin α1 knock-down cells, as well as the NBS1 knock-down cells, showed a significant number of multinucleated cells, which indicated abnormal chromosome breakages and cell-cycle control ( Figure 3F).…”
Section: Pre-s 2 Mutant Lhbs Inhibits Nbs1-mediated Dna Homologous Rementioning
confidence: 99%
“…B, Quantification of the numbers of γ-H2AX foci per embryo in control and SETD2-KD group was analyzed (total number of embryos analyzed: n = 13 for control; n = 13 for SETD2-KD). 31 If the degree of damage is beyond the competence of recovery, cells never enter mitosis but undergo apoptotic cell senescence or death. *P < .05 vs control.…”
Section: Setd2-kd Results Lowered Trimethylation Level Of Histone Hmentioning
confidence: 99%